Flexible Coordination of Stationary and Mobile Conversations with Gaze: Resource Allocation among Multiple Joint Activities - Mayor, Eric; Bangerter, Adrian (Frontiers in Psychology, 2016)
Gaze is instrumental in coordinating face-to-face social interactions. But little is known about gaze use when social interactions co-occur with other joint activities. We investigated the case of walking while talking. We assessed how gaze gets allocated among various targets in mobile conversations, whether allocation of gaze to other targets affects conversational coordination, and whether reduced availability of gaze for conversational coordination affects conversational performance and content. In an experimental study, pairs were videotaped in four conditions of mobility (standing still, talking while walking along a straight-line itinerary, talking while walking along a complex itinerary, or walking along a complex itinerary with no conversational task). Gaze to partners was substantially reduced in mobile conversations, but gaze was still used to coordinate conversation via displays of mutual orientation, and conversational performance and content was not different between stationary and mobile conditions. Results expand the phenomena of multitasking to joint activities.